OIL, REGIME CHANGE AND AMERICA’S INVASION OF IRAQ: A POST-MORTEM ANALYSIS - Onuoha, Jonah (University of Nigeria Journal of Political Economy, 2022)
Saddam Hussein was captured in December 2003, and on November, 2006, he was convicted. He faced the hangman on December 30, 2006. Even though Iraq has witnessed huge harvest of seven oil related wars, the 2003 invasion has generated a hot debate on why the United States invaded Iraq. This essay is a contribution to the debate. The paper argues that even though the reason for the attack are spurious, Iraq under Saddam Hussein, actually constituted a serious threat to US foreign policy in the Middle East. Consequently, the real and unspoken reason for the invasion is oil and regime change, rather than the search for weapons of mass destruction. It warns that if US troops are withdrawn by the end of 2011, Iraq may relapse into a protracted civil war or, a failed state.